1999
DOI: 10.3354/ame020095
|View full text |Cite
|
Sign up to set email alerts
|

Structure and dynamics of the pelagic microbial food web of the Subtropical Convergence region east of New Zealand

Abstract: The Subtropical Convergence (STC) region to the east of New Zealand was sampled in both winter and spring to establish the food web structure and dynamics in 3 water masses. Subtropical (ST) waters to the north were warm with high salinity, and in spring macronutrient concentrations were potentially limiting to phytoplankton growth. Subantarctic (SA) waters to the south in both seasons were cold, with lower salinity and high macronutrient concentrations with chlorophyll a concentrations of 0.12 to 0.19 pg 1-'.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
24
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 47 publications
6
24
1
1
Order By: Relevance
“…Phytoplankton are iron‐limited and dominated by picophytoplankton [ Bradford‐Grieve et al , 1997, 1999; Boyd et al , 1999]. The biota are mainly components of the microbial food web in this pelagic ecosystem [ James and Hall , 1998; Hall et al , 1999, 2004] with correspondingly low export rates of biogenic material [ Nodder and Northcote , 2001].…”
Section: Introductionmentioning
confidence: 99%
“…Phytoplankton are iron‐limited and dominated by picophytoplankton [ Bradford‐Grieve et al , 1997, 1999; Boyd et al , 1999]. The biota are mainly components of the microbial food web in this pelagic ecosystem [ James and Hall , 1998; Hall et al , 1999, 2004] with correspondingly low export rates of biogenic material [ Nodder and Northcote , 2001].…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations in winter and spring reported that during both seasons in the subantarctic waters, and in the subtropical waters during spring, the microbial food web was the dominant pathway for carbon and energy flows (James et al 1996, Hall et al 1999. During these periods the majority of phytoplankton biomass was found to be in the 1 2 0 pm size class and bacterial biomass dominated phytoplankton carbon (Hall et al 1999). In this late summer study chl a was generally low, reflecting oligotrophic conditions (Table l ) , and the majority of phyto- Table 3.…”
Section: Role Of the Microbial Food Web In The Convergence Zonementioning
confidence: 99%
“…In the present study, the most plausible reason causing the little enhancement of the export flux would be related to microzooplankton grazing. Indeed, Hall et al (1999) demonstrated that >78 % of daily PP can be grazed by microzooplankton in the STF in austral spring and winter. In contrast, mesozooplankton grazing is likely to be in the order of only 1-2 % of daily PP (Bradford-Grieve et al, 1998).…”
Section: Poc/ 234 Th Ratios and Poc Export Fluxmentioning
confidence: 99%